Putting Cosmogony into Words: The Neoplatonists on Metaphysics and Discourse (logos) - Motta, Anna (Peitho. Examina Antiqua, 2019)
The present paper focuses on some aspects of the Neoplatonist literary-metaphysical theory, which has clearly been expressed in the anonymous Prolegomena to Plato’s philosophy and further confirmed in Proclus’ exegesis of the Timaeus. Thus, this contribution, examines and compares several passages from the Prolegomena and from Proclus’ Commentary on the Timaeus with a view to showing that it is legitimate to speak of a certain cosmogony of the Platonic dialogue that is analogous to that of the macrocosm. Moreover, the analogy between macrocosm and microcosm makes it possible to further investigate the similarity between the λόγος-ζῷον of the Demiurge and that of Timaeus, on the one hand, and the reality which the λόγος expresses, on the other. This similarity turns out to be both structural/morphological and content-related/semantic. Thus, by combining the natural and theological science, the analysis of the “generation” of the macrocosm and microcosm brings out the strongly analogical nature of Plato’s dialogues, which is particularly visible in the Timaeus.